2012
DOI: 10.1038/ejcn.2012.169
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25-hydroxyvitamin D and markers of insulin resistance in a Japanese working population

Abstract: BACKGROUND/OBJECTIVES:The association between vitamin D status and insulin resistance (IR) has been less studied among Asians, and it remains elusive whether calcium could modify such an association. We examined the association of serum 25-hydroxyvitamin D (25(OH)D) concentrations with IR markers and the potential effect modification by calcium intake among a Japanese population. SUBJECTS/METHODS: The authors analyzed data (n ¼ 494) from a cross-sectional survey conducted in 2009 among a Japanese working popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 45 publications
3
16
1
Order By: Relevance
“…In a healthy Cree community in Quebec, Canada, no association between serum 25(OH)D and insulin homeostasis indices (HOMA-IR and HOMA-beta) was detected 14. Moreover, even in the Asian studies that reported an inverse association between 25(OH)D and insulin resistance, the association was limited to participants who were overweight or obese 8,9. Lastly, a randomized double-blinded trial in women with polycystic ovary syndrome and vitamin D deficiency also did not find vitamin D supplementation to have any effect on insulin resistance 13…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…In a healthy Cree community in Quebec, Canada, no association between serum 25(OH)D and insulin homeostasis indices (HOMA-IR and HOMA-beta) was detected 14. Moreover, even in the Asian studies that reported an inverse association between 25(OH)D and insulin resistance, the association was limited to participants who were overweight or obese 8,9. Lastly, a randomized double-blinded trial in women with polycystic ovary syndrome and vitamin D deficiency also did not find vitamin D supplementation to have any effect on insulin resistance 13…”
Section: Discussionmentioning
confidence: 91%
“…Several epidemiologic studies have reported associations between lower circulating vitamin D levels and impaired glucose homeostasis 1,6,7,8,9. Analysis of the U.S. National Health and Nutrition Examination Survey datasets revealed that insufficient serum 25(OH)D concentration is significantly associated with type 2 diabetes and insulin resistance 6.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased insulin resistance is found associated with low vitamin D status in a variety of observational studies, for instance, population-based studies in geographically diverse countries [111,112]. Hypponen and Power [109] reported a statistically significant negative association between vitamin D status and hemoglobin A1c.…”
Section: Methodsmentioning
confidence: 99%